Crystal engineering for intramolecular pi-pi stacking: effect of sequential substitution of f on molecular geometry in conformationally flexible sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Kumar, Deepak; Kotmale, Amol; Gonnade, Rajesh G.; Stuerzer, Tobias (Crystal Growth & Design, 2019)
A small library of ten sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of chronological positioning of the F-atom on the intramolecular pi-stacking assembly. The sequential positioning of F atoms was carried out on one of the aromatic rings that is linked to the sulfonamide moiety directly while the other aromatic ring (phenyl or pyridine) is linked by an ethyl spacer with the sulfonamide moiety. The ethyl spacer is provided to achieve the required flexibility so that both aromatic rings can bend to acquire syn conformation facilitated pi-stacking between electron-deficient and electron-rich aromatic rings. The idea was to study the interplay between hydrogen bonding and pi-stacking synthons in the conformationally flexible sulfonamide derivatives. The solid-state conformation of all the derivatives was investigated using the single-crystal X-ray diffraction technique. Crystal structure analysis revealed that the syn conformation was achieved only in trifluoro and pentafluoro sulfonamide derivatives with benzene substitution while in all other derivatives the molecules take either midway or anti conformations. None of the sulfonamide molecules with a pyridine moiety showed syn conformation. It could be because of the involvement of the pyridine N-atom in the hydrogen bonding dimeric synthon. The molecular conformation study in solution state using 2D NOESY and HOESY NMR experiments also substantiated syn conformation in a pentafluoro sulfonamide molecule with benzene substitution. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed higher stability for the syn conformation over midway and anti orientations.